2018
DOI: 10.1103/physrevb.97.104422
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Snell's law for spin waves in heterochiral magnetic films

Abstract: Thin ferromagnetic films with an interfacially-induced Dzyaloshinskii-Moriya interaction (DMI) exhibit non-trivial asymmetric dispersion relations that lead to unique and useful magnonic properties. Here we derive an analytical expression for the magnon propagation angle within the micromagnetic framework and show how the dispersion relation can be approximated with a comprehensible geometrical interpretation in the k-space of the propagation of spin waves. We further explore the refraction of spin waves at DM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 38 publications
(59 reference statements)
1
24
0
Order By: Relevance
“…2(a). Similar results have been presented for spin waves propagation in different magnetic systems [45,46]. For instance, the generalized Snell's law describes the spin wave refracted at the domain wall in a chiral magnetic film in Ref.…”
Section: The Linear Dynamics Of Spin Waves In Homogeneous and Hetsupporting
confidence: 76%
“…2(a). Similar results have been presented for spin waves propagation in different magnetic systems [45,46]. For instance, the generalized Snell's law describes the spin wave refracted at the domain wall in a chiral magnetic film in Ref.…”
Section: The Linear Dynamics Of Spin Waves In Homogeneous and Hetsupporting
confidence: 76%
“…In particular, this numerical technique can be used to calculate the spectrum of spin waves, and when a DMI is present, it reveals different properties characteristic of these systems, such as the spin-wave asymmetry. In this context, simulations have successfully supported theoretical formulations [80,96,97,99,[132][133][134][135][136][137] and experimental measurements [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87]138] on thin-film systems with a homogeneous DMI. A micromagnetic simulation is based on numerically discretizing the continuum description of the magnetic system into a mesh of magnetic moments whose arrangement depends on the discretization method.…”
Section: Micromagnetic Simulations Of Spin Waves With Interfacial Dmimentioning
confidence: 64%
“…A main aspect of this confinement at relatively low frequencies is the formation of a caustic beam [10][11][12]. Additionally, it has been shown that refractive spin-wave optics can be realized [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%